Inquiry into life - Mader, Sylvia S. (McGraw-Hill, 2006)
From the unique delivery of biology content, to the time tested art program, to the complete integration of the text with technology, Dr. Sylvia Mader has formed a teaching system that will both motivate and enable your students to understand and appreciate the wonders of all areas of biology.